Nonlocal effects of antibiotic-resistance-causing mutations reveal an alternative region for targeting on FtsW-penicillin-binding protein 3 complex of haemophilus influenzae - Alhamwi, Almotasem Belah; Atılgan, Canan; Şensoy, Özge (American Chemical Society, 2023)
[Abstract Not Available]
Keywords: Haemophilus influenzae; Alternative Region; FtsW-Penicillin-Binding Protein 3 Complex